2003
DOI: 10.1136/pmj.79.931.292
|View full text |Cite
|
Sign up to set email alerts
|

How valuable is ascitic cytology in the detection and management of malignancy?

Abstract: Introduction: Ascitic cytology is often requested in the early stages of ascitic assessment. A review of this practice in a major English teaching hospital is presented. Method: Patients were retrospectively identified using the histopathology and patient administration system between January 1999 and May 2001. Results: Of 276 samples sent for assessment 35 cases were found to be negative when on further review an intra-abdominal malignancy was present. The malignancy was diagnosed using a radiological modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 17 publications
4
37
0
Order By: Relevance
“…There is no published literature documenting the specific sensitivity of peritoneal fluid analysis for malignant ascites in metastatic NET, but there is a published 60% sensitivity for ascitic cytology with any intra-abdominal malignancy. 25 The putative etiology for the development of ascites after PRRT is possibly a presinusoidal portal hypertension with exacerbation by radionuclide toxicity. Studies have shown hepatocellular apoptosis and peribiliary fibrosis after chemoembolization.…”
Section: Discussionmentioning
confidence: 99%
“…There is no published literature documenting the specific sensitivity of peritoneal fluid analysis for malignant ascites in metastatic NET, but there is a published 60% sensitivity for ascitic cytology with any intra-abdominal malignancy. 25 The putative etiology for the development of ascites after PRRT is possibly a presinusoidal portal hypertension with exacerbation by radionuclide toxicity. Studies have shown hepatocellular apoptosis and peribiliary fibrosis after chemoembolization.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the sensitivity of ascitic cytology is approximately 60%, with a specificity of 100%. 2 Two thirds of patients with malignant-related ascites have PC, and 96.7% of patients with PC have positive ascitic fluid cytology. 3 Direct visualization by laparoscopy, although minimally invasive, has its limitations, such as tumor seeding and associated morbidity.…”
mentioning
confidence: 99%
“…This study is in agreement with Udasimath et al study 7 . Studies by Hwangbo et al, Khan et al and Mahmood et al 8,9,10 in their studies reported liver cirrhosis to be the most common etiology amongst non-malignant causes of ascites. As seen in their studies, liver was the most common setting for ascites as in our study.…”
Section: Discussionmentioning
confidence: 93%